1999
DOI: 10.1007/s000110050517
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a ∼100 kD protein with strong immunoreactivity to antibodies specific for inducible nitric oxide synthase (iNOS) but without NOS activity in neutrophils of patients suffering from sepsis: Results of a preliminary study

Abstract: The detection of an approximately 100 kD protein with immunoreactivity to antibodies recognizing human iNOS but without NOS activity in neutrophils of patients with sepsis should initiate studies to elucidate the origin and function of this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Our study also found a protein band at approximately 100 kDa in several cases. This band has also been reported by other workers who studied NOS2 expression in neutrophils from patients with septic shock (22). It was concluded that further studies were required to elucidate the nature of this protein.…”
Section: Discussionsupporting
confidence: 82%
“…Our study also found a protein band at approximately 100 kDa in several cases. This band has also been reported by other workers who studied NOS2 expression in neutrophils from patients with septic shock (22). It was concluded that further studies were required to elucidate the nature of this protein.…”
Section: Discussionsupporting
confidence: 82%
“…Inactivated resting rodent neutrophils and macrophages have very low or nondetectable expression of iNOS2, and expression is greatly enhanced upon activation (Nair et al 2003;McCafferty et al 1999;Richter et al 1999).…”
Section: Eosinophil Antigens: Major Basic Proteinmentioning
confidence: 99%
“…Inducible NO synthase 2 (iNOS2) is a cytoplasmic biomarker of activated neutrophils and macrophages activated by CD4Th1 proinflammatory cytokines IFN-gamma and TNF-alpha (Figure 34). Inactivated resting rodent neutrophils and macrophages have very low or nondetectable expression of iNOS2, and expression is greatly enhanced upon activation (Nair et al 2003; McCafferty et al 1999; Richter et al 1999).…”
Section: Tissue Histiocyte (Macrophage) Antigens: Cd68 Cd163 F4/80 Iba1 Lysozyme Mac2 Mac3 S100p Arginase 1 Inos2 Ym1mentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates the findings of Wheeler et al, who reported that deoxycholate was superior to other detergents for the extraction of neutrophil NOS II, which they found to be tightly membrane bound to >90% (13). Thus, failure to demonstrate a 130 kD protein corresponding to NOS II in whole cell lysates of neutrophils (7, 8, 20, 21) may be explained both by insufficient proteinase inhibition and by insufficient release of the membrane‐bound enzyme.…”
Section: Discussionmentioning
confidence: 99%